Respuestas

2014-03-07T00:46:39+01:00
Simple.

a) 8x-6+3x=7x+x+14
8x+3x-8x=14+6
3x=20
x=20/3


b) x+3(x-1)=6-4(2x+3)
x+3x-3=6-8x-12
x+3x+8x=6-12+3
12x=-3
x=-3/12

espero ayude
  • Usuario de Brainly
2014-03-07T00:51:09+01:00
8x +3x -7x - x  = 14 + 6                      x + 3x - 3 = 6 -8x + 12 
3x =  20                                             x + 3x + 8x  =  6+12 +3 
x 20 / 3                                               12 x =  21
x = 6.6                                                     x =  21 / 12 
                                                                x  =  1.75